An evaluation of the use of investigations in a nurse-led rapid access chest pain clinic. (2nd December 2021) - Kwok, Chun Shing; Jackson, Debbie; Bennett, Sadie; Tafuro, Jacopo; Large, Adrian; Mallen, Christian D; Smith, Dot-Morgan; Duckett, Simon
Abstract : Background/Aims: Chest pain is a common symptom, but its presentation and cause varies widely, making diagnosis a challenge. This study describes the authors' experience of a nurse-led rapid access chest pain clinic, and associated use of investigation and patient outcomes. Methods: A retrospective service evaluation of patients referred to a nurse-led rapid access chest pain clinic was performed. Routinely-recorded data on patient demographics, symptoms, comorbidities, medications, cardiology clinic attendances and investigations were collected. In addition, admissions to accident and emergency or inpatient, death, acute myocardial infarction and percutaneous coronary intervention within 1 year were obtained. Results: A total of 279 patients were included in the evaluation between January and February 2019. Chest pain was present as a symptom in 92.8% of patients, while 37.6% of patients had shortness of breath. Only 16.8% had typical angina, while 34.4% had atypical angina. The majority (93.9%) had two or fewer cardiology clinic appointments, the most common imaging investigation used was computed tomography coronary angiogram (47.3%) and 8.2% had a stress echocardiogram or invasive angiogram. Approximately one in five patients had a hospital admission within 1 year. The mortality rate within 1 year was 1.4%, but were all non-cardiac causes. Only 3.6% underwent percutaneous coronary intervention and there was only one mortality. Conclusions: This service evaluation shows that a nurse-led rapid access chest pain clinic can be safe, efficient and closely adhere to National Institute for Health and Care Excellence guidelines. Many patients do not require unnecessary and potentially harmful investigations and revascularisation rates are low.